Book Review: Tablets at Work by Claudia Wollny - Silvia Ungerechts (EXARC Journal)
This 700-plus page book is dedicated to the exploring the basics of tablet weaving. This book will not only allow the reader to understand the step-by-step methods for different tablet weaving techniques but also describes the process behind creating one’s own pattern.